2017
DOI: 10.1038/s41598-017-14241-y
|View full text |Cite
|
Sign up to set email alerts
|

Akap350 Recruits Eb1 to The Spindle Poles, Ensuring Proper Spindle Orientation and Lumen Formation in 3d Epithelial Cell Cultures

Abstract: The organization of epithelial cells to form hollow organs with a single lumen requires the accurate three-dimensional arrangement of cell divisions. Mitotic spindle orientation is defined by signaling pathways that provide molecular links between specific spots at the cell cortex and astral microtubules, which have not been fully elucidated. AKAP350 is a centrosomal/Golgi scaffold protein, implicated in the regulation of microtubule dynamics. Using 3D epithelial cell cultures, we found that cells with decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Thus, it is conceivable that if the cells divide in the wrong plane, either due to misalignment of the microtubule spindle or cleavage furrow ingression direction, erroneous lumens may arise from each cell division. There are a number of proteins known to regulate spindle orientation during lumen expansion, including Cdc42 and its GEFs and GAPs 5457 , polarity complex proteins 55,58 , phosphatidylinositol phosphatases 59 , microtubule binding proteins 60 , and other small GTPases 61 . Consequently, while apical membrane biogenesis is crucial for lumen formation, proper orientation of later cytokinesis events is also essential for expansion and maintenance of a single lumen.…”
Section: Lumen Formation In Vitromentioning
confidence: 99%
“…Thus, it is conceivable that if the cells divide in the wrong plane, either due to misalignment of the microtubule spindle or cleavage furrow ingression direction, erroneous lumens may arise from each cell division. There are a number of proteins known to regulate spindle orientation during lumen expansion, including Cdc42 and its GEFs and GAPs 5457 , polarity complex proteins 55,58 , phosphatidylinositol phosphatases 59 , microtubule binding proteins 60 , and other small GTPases 61 . Consequently, while apical membrane biogenesis is crucial for lumen formation, proper orientation of later cytokinesis events is also essential for expansion and maintenance of a single lumen.…”
Section: Lumen Formation In Vitromentioning
confidence: 99%
“…Several lines of evidence indicated that the microtubule plus-end binding protein EB1 plays a critical role in defining the spindle position. Through mediating the interaction between microtubule ends, the cell cortex, and dynein motors, EB1 is involved in spindle assembly, dynamic, and positioning of the spindle [22][23][24]. Intriguingly, in our immunoprecipitation (IP) experiment using SIK2 antibodies, EB1 was found to precipitate with SIK2 in G2-synchronized SKOV-3 cells (Figure 3H).…”
Section: Inhibition Of Sik2 Altered the Positioning Of The Mitotic Spindlementioning
confidence: 79%
“…Accordingly, the removal of mature centriole-specific proteins, including ninein (Wang et al, 2009), WDR62 and ASPM (Gai et al, 2016;Jayaraman et al, 2016), is sufficient to cause premature depletion of progenitor cells from the VZ and to impair CNS growth. Other proteins are recruited to the centrosome in a microtubule-independent manner by interacting with scaffold proteins, such as AKAP9 and pericentrin (Gillingham and Munro, 2000), which contain a localization domain (PACT domain) that targets the centrosome and serves to recruit structural and regulatory components such as γ-tubulin, microtubule binding proteins and signalling enzymes involved in microtubule nucleation (Almada et al, 2017). Supporting the relevance of centrosomal scaffold proteins in the control of the mode of NPC division, the removal of pericentrin triggers neurogenic divisions both in the chick spinal cord (Saade et al, 2017) and in the developing mouse cortex (Buchman et al, 2010).…”
Section: Intrinsic Centrosomal Asymmetries In Dividing Neural Progenimentioning
confidence: 99%